Law, Economics and the Draft Takeovers Code - Dugan, Robert (Victoria University of Wellington Law Review, 1996)
In August 1995, the Government announced that it would defer a decision whether to adopt the draft Takeovers Code that had been formulated and recommended by the Takeovers Panel pursuant to s 19 of the Takeovers Act 1993. This announcement culminates, at least for the time being, almost a decade of intense and sometimes acrimonious controversy over the regulation of takeovers in New Zealand. Economics-based arguments figured in the run up to the legislation, within the legislation itself, in the formulation of the Code and in the debate about its merits. After a review of the background and the principal features of the draft Code, this article considers the main issues in the law and economics debate that preceded the Government's decision. The author argues that the Government's decision to defer action on the Draft Code can likely be attributed to the "law and economics" opposition to takeovers regulation and the Code itself. The article concludes that both law and economic components were flawed: the legal component (i.e. that there are already existing companies legislation and listing requirements) ignores the fact that takeover regimes fill a regulatory gap, and the economic component (i.e. that the cost of takeovers will increase) fail to consider the total effect of an arrangement.